A critical analysis of the principles relating to simulated transactions in the context of the case of commissioner for the South African revenue services v NWYK limited 73 SATC 55 - Louw, C (Adv.) (University of Pretoria, 2014)
Dissertation (LLM)--University of Pretoria, 2013.